Association of Serum Cystatin C with Pre-eclampsia: A Case Control Study - Akhter, Nasima; Deeba, Farzana; Nasrin, Begum; Chowdhury, Saleha Begum (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Background: Cystatin C, an endogenous marker of renal function, which increases in pregnancy as more so in pre-eclampsia, studies show it may be marker of pre-eclampsia. Objective (s): The objective of the present work was to investigate the association between serum cystatin C levels in normal and pre-eclamptic pregnancy. Methods and material: This case control study was conducted in the department of obstetrics and gynaecology in three tertiary care hospitals of Dhaka city (BSMMU, DMC, BIRDEM ) during the period from January 2009 to December 2010. A total 240 women of 20-40 wks of pregnancy were enrolled in the study. One hundred and twenty four women of pre-eclampsia were recruited as case and 116 healthy pregnant women were enrolled as control. Serum cystatin C was measured in both case and control by a fully automated particle-enhanced immune-turbidimetric assay for cystatin C in undiluted samples. Serum cystatin C level was compared between the groups. P value reached from unpaired student t-test and chi square test by analyzing the data. P value less than 0.05 was considered to be significant. Results: The mean (±SD) serum cystatin C levels in case group was 1.17±0.34 mg/lranged from 0.1-2.2 mg/l. In control groups the mean (±SD) serum cystatin C level was 0.87±0.31 mg/l, ranged from 0.24-1.98 mg/l, which was significantly higher (p<0.001) in case. There was statistically significant association between serum cystatin C and pre-eclampsia. Serum Cystatin C level >1mg/l was found in more than half (69%) of the cases compared to 25% of the control group (p<0.001). Computation of odds ratio reveals that the cases had 6.79 times higher risk of having pre-eclampsia than that of the control group (p<0.001). Conclusion: There is significant association between pre-eclampsia and serum cystatin C Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 29-32